Do foreign investors exhibit a corporate governance disadvantage? An information asymmetry perspective - Kang, Jun-Koo (2013)
Although foreign equity ownership around the world has increased substantially over the last three decades, there is little evidence on the role of foreign ownership in the host country. Using a large sample of foreign partial acquisitions in the US from 1981 to 1999, we examine the determinants of foreign acquirers’ governance activities in US targets. We focus on the information asymmetries that foreign acquirers face in the US as a key determinant of their governance activities in US targets, and hypothesize that such information asymmetries provide them with weak incentives to engage in governance activities. Consistent with our hypothesis, we find that foreign acquirers whose countries share a common language and a common culture with the US are more likely to engage in post-acquisition governance activities than are other foreign acquirers. Moreover, the probability of foreign acquirers’ governance activities is positively related to their previous acquisition activities in the US, but negatively related to the physical distance from the targets and the difference in shareholder rights scores between the US and their home countries. Our results suggest that information asymmetries that foreign acquirers face in the host country are an important determinant of their governance activities in domestic targets.